Optimizing water use in spring maize through integrated agro-techniques in groundwater-stressed regions of northwestern India - Khushkarandeep Singh; Vinay Kumar Sindhu; Ajmer Singh Brar; J.S. Lamba; J.S. Deol; R.S. Jakhar; Ranjeet Singh (Agricultural Water Management, 2025)
Agriculture consumes nearly 80 % of India's freshwater, and the expansion of spring maize, a newly introduced water-intensive crop, is exacerbating groundwater depletion in northwestern India. This study, conducted at Centre for Water Technology and Management, Punjab Agricultural University, Ludhiana, in 2023 and 2024, aimed to strategically integrate available agro-techniques for efficient water use in spring maize, promoting sustainable production. A split-plot field experiment assessed two maize hybrids (DKC 9108, DKC 9208) and eight combinations of different planting methods [ridge planting and pneumatic broad-bed planting], mulching [straw mulch at 9 t/ha and plastic mulching], irrigation methods [furrow irrigation, surface drip irrigation (SDI), sub-surface drip irrigation (SSDI)] and irrigation scheduling [irrigation at 1.0 IW:CPE, 1.2 IW:CPE, 80 % ETc, 100 % ETc and at 30 % depletion of available moisture (DASM)]. The results showed that both the spring maize hybrids, exhibited similar growth and yield across both years. Similarly, ridge planting with furrow irrigation and pneumatic broad-bed planting with furrow irrigation resulted in comparable grain yield across the years. However, latter resulted in 9–20 % saving of irrigation water with 11–26 % higher apparent water productivity (AWP). Integrating pneumatic broad-bed planting with SDI without straw mulching did not significantly increase the grain yield of spring maize during both years but saved 26–27 % irrigation water and improved AWP by 43–44 %, however, during 2024, SSDI without straw mulch increased the grain yield by 7 %, with 14 % saving of irrigation water and 25 % higher AWP compared to furrow irrigation in pneumatic broad-bed planting. Further, integrating straw mulch at 9 t/ha and pneumatic broad-bed planting with either SDI or SSDI had no significant effect on grain yield during 2023, but increased the grain yield by 9–13 % and net returns by 10–16 % as compared to SDI or SSDI without straw mulch in 2024. In conclusion, the combination of pneumatic broad-bed planting with straw mulch at 9 t/ha and SSDI at 30 % DASM increased grain yield by 16–19 % and 15–18 %, AWP by 35–73 % and 22–37 %, and net returns by 20–27 % and 18–24 %, while saving 14–31 % and 6–14 % irrigation water, and 20 % fertilizers compared to ridge planting with furrow irrigation and pneumatic broad-bed with furrow irrigation, respectively.